South African Renal Registry Annual Report 2021 - Davids, M Razeen; Marais, Nicola; Sebastian, Sajith; Jardine, Thabiet; Jacobs, Julian C (African Journal of Nephrology, 2023)
This is the tenth consecutive annual report of the South African Renal Registry since it was re-established and launched with the publication of the December 2012 data on kidney replacement therapy (KRT) in South Africa. The December 2021 data reported here indicate a stabilisation of the COVID-19-related decrease in patient numbers which was recorded in the previous report. There were 849 patients who started KRT in 2021, an incidence of 14.1 per million population (pmp). Most of these patients (80%) were treated in private centres. In December 2021, the total number of patients on treatment with chronic dialysis or transplantation stood at 8 866, up from 8 734 in 2020, an overall prevalence of 147 pmp. The prevalence was 736 pmp in the private healthcare sector. In the public sector, the overall prevalence was 45 pmp, with the Western Cape being the province with the highest prevalence (166 pmp) and Mpumalanga the province with the lowest (3 pmp).